Interaksi Sosial Masyarakat Dayak dan Madura di Kuala Pembuang 1 Kabupaten Seruyan Pasca Kerusuhan Sampit Tahun 2006-2017 - Sukmana, Wulan Juliani; Anis, Mohammad Zaenal Arifin; Mansyur, Mansyur (Lambung Mangkurat University, 2024)
The tragedy of the Sampit riots that occurred in 2001 has changed the life order of the people of Central Kalimantan, especially areas close to the location of the conflict. The difficulty of building communication again after the conflict involving the Dayak and Madurese communities is a sign of how much trauma is felt by the community, especially those who saw the incident firsthand. The purpose of this study is to find out how the background of the Sampit riots in the Kuala Pembuang area and find out how social interactions were built between the Dayak and Madurese communities after the 2001 Sampit riots in Kuala Pembuang in 2006-2017. This research uses historical methods consisting of Heuristics, namely collecting data through observation, interviews, and collecting documents, books a.nd archives related to the tragedy of the Sampit riots in 2001, then continued at the stage of source criticism, evaluating sources that have been collected and validating the truth of these sources, Continued at the stage of interpretation, namely interpreting the facts that have been obtained and then after that assembling them into historical stories called historiography. The results showed that the sampit riots reached as far as the city of Kuala Pembuang caused by rebellion and provocation by elements of Madurese. However, after the outbreak of the Sampit riots, Dayak residents in Kuala Pembuang were able to receive the arrival of Madurese, and re-establish interaction with the social processes that occur among the people of Kuala Pembuang. The conclusion in this study is that the people of Kuala Pembuang can re-establish social interaction after the Sampit riot conflict that occurred through social processes.